We are Telling the World Everything the Cerebral Cortex Memorises - Zhang Yue (Britain International for Academic Research (BIAR) Publisher, 2020)
The cognitions and thoughts of a human brain are accomplished by the neurons to transmit informations in brain. If we want to know the thoughts of a brain, we must to contact the neural network of the brain. One of the well-known way is to penetrate the capillary holes of the surface of the brain with electromagnetic waves to contact neurons. The modern method is to emit electromagnetic waves with radar via the GPS which can make lights exactly and easily pass through the capillary holes of the brain.The paper will simply describe the principle of their works.